2021
DOI: 10.1128/jvi.00521-21
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Membrane Topology and Retention Signal of Pestiviral Glycoprotein E1

Abstract: Pestiviruses are members of the family Flaviviridae, a group of enveloped viruses that bud at intracellular membranes. Pestivirus particles contain three glycosylated envelope proteins, Erns, E1 and E2. Among them, E1 is the least characterized concerning both biochemical features and function. E1 from bovine viral diarrhea virus (BVDV) strain CP7 was analyzed with regard to its intracellular localization and membrane topology. Here, it is shown that even in the absence of other viral proteins, E1 is not secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…However, secretion of the truncated polypeptides was not detectable (Figure 1C). For E1 (construct pYM-93), a low amount of secreted protein could be observed after prolonged exposure time [23], whereas the C-terminally truncated E1 lacking residues 179 to 195 or 166 to 195 (constructs pYM91 or pYM-92, respectively) was not detectable at all in our experimental system (Figure 1C). The lower amounts detected for constructs pYM-92 and pYM-93 might therefore result from instability of the truncated proteins.…”
Section: Pestiviral Glycoprotein E1 Can Form Homooligomers Independent Of Its Membrane Anchormentioning
confidence: 75%
See 4 more Smart Citations
“…However, secretion of the truncated polypeptides was not detectable (Figure 1C). For E1 (construct pYM-93), a low amount of secreted protein could be observed after prolonged exposure time [23], whereas the C-terminally truncated E1 lacking residues 179 to 195 or 166 to 195 (constructs pYM91 or pYM-92, respectively) was not detectable at all in our experimental system (Figure 1C). The lower amounts detected for constructs pYM-92 and pYM-93 might therefore result from instability of the truncated proteins.…”
Section: Pestiviral Glycoprotein E1 Can Form Homooligomers Independent Of Its Membrane Anchormentioning
confidence: 75%
“…We have shown that there is a dynamic membrane topology change of the transmembrane region of E1 after signal sequence cleavage with a relocation of the E1 Carboxyterminus from the ER to the cytosolic side [23]. This is also true for E2 of pestiviruses [22] and the closely related HCV envelope proteins [32].…”
Section: E1/e2 Heterodimer Formation Is Independent Of the Transmembrane Region Of E1mentioning
confidence: 75%
See 3 more Smart Citations